2021
DOI: 10.1371/journal.pone.0254368
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a novel ferroptosis-related gene model for predicting the prognosis of gastric cancer patients

Abstract: Background Ferroptosis is a novel form of regulated cell death that plays a critical role in tumorigenesis. The purpose of this study was to establish a ferroptosis-associated gene (FRG) signature and assess its clinical outcome in gastric cancer (GC). Methods Differentially expressed FRGs were identified using gene expression profiles from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database. Univariate and least absolute shrinkage and selection operator (LASSO) Cox regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Currently, surgery, chemotherapy, and targeted therapy have been widely used for CRC treatment, whereas some patients still exhibit resistance to these therapies [90]. A recent study confirmed that ferroptosis might be a substitute strategy for killing chemotherapy-resistant CRC cells [70]. In addition, mounting evidence suggests that ferroptosis-related genes could be used as biomarkers to predict CRC (Table 3).…”
Section: The Role Of Ferroptosis In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Currently, surgery, chemotherapy, and targeted therapy have been widely used for CRC treatment, whereas some patients still exhibit resistance to these therapies [90]. A recent study confirmed that ferroptosis might be a substitute strategy for killing chemotherapy-resistant CRC cells [70]. In addition, mounting evidence suggests that ferroptosis-related genes could be used as biomarkers to predict CRC (Table 3).…”
Section: The Role Of Ferroptosis In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…FRGs-based signatures had been identified with prognostic values in colon cancer, [ 51 ] lung adenocarcinoma, [ 52 , 53 ] gastric cancer, [ 54 ] breast cancer, [ 55 ] and bladder cancer. [ 21 , 56 ] And nomograms built by FRGs for predicting survival probabilities had already been used in lung adenocarcinoma and oral squamous cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…130 Furthermore, other researchers utilizing similar methods have identified several genes associated with ferroptosis, with their findings converging on a pivotal gene, namely ZFP36. [131][132][133][134] ZFP36 is an RNA-binding protein targeted for degradation by FBXW7/CDC4 E3 ubiquitin ligase that plays a part in triggering ferroptosis in hepatic stellate cells (HSCs).…”
Section: Prognostic and Diagnostic Markers Associated With Ferroptosi...mentioning
confidence: 99%